Wound healing and pain evaluation following diode laser surgery vs. conventional scalpel surgery in the surgical treatment of oral leukoplakia: a randomized controlled trial - de Pauli Paglioni, Mariana; Pedroso, Caique Mariano; Faustino, Isabel Schausltz Pereira; Vargas, Pablo Agustin; de Goes, Mario Fernando; Martins, Manoela Domingues; Lopes, Márcio Ajudarte; Santos-Silva, Alan Roger (Frontiers in Oral Health, 2025)
ObjectivesThis study aimed to compare patient-reported pain scores and clinician-assessed healing outcomes following the treatment of oral leukoplakia (OL) with a diode laser vs. a conventional scalpel.MethodsA randomized, double-blind clinical trial (Brazilian Clinical Trials Registry (RBR-7pgcyq) was conducted involving histopathologically confirmed OL patients. Participants were randomly allocated to undergo treatment with either a diode laser or a scalpel. Pain was assessed at 24 h, 48 h, and 7 days using the Visual Analog Scale (VAS), while healing outcomes were clinically evaluated at 7 days, 1-month, and 3-months post-treatment using the Vancouver Scar Scale. Statistical analyses included the Mann–Whitney U-test for comparing pain and healing scores between interventions. Friedman test also was used to analyze healing progress over time.Results64 patients were analyzed (33 in diode laser and 31 in scalpel group). No significant differences in pain scores were observed between the treatment groups at 24 h (p = 0.75), 48 h (p = 0.92), or 7 days (p = 0.44). Overall, pain levels varied significantly by OL location at 24 h (p = 0.001), 48 h (p = 0.01), and 7 days (p = 0.03), with tongue lesions associated with significantly higher pain compared to gingival lesions at 24 h (p = 0.005) and 48 h (p = 0.01), as well as compared to palatal lesions at 24 h (p = 0.01). Laser group showed significantly better healing compared to the scalpel group at 7 days (p = 0.01), with no significant differences observed at 1 month (p = 0.67) or 3 months (p = 0.25). Healing outcomes improved significantly over time in both arms (p < 0.001).ConclusionsThere was no significant difference between the diode laser and scalpel treatment arms regarding post operative pain scores. Diode lasers represent better healing at the first week post treatment, but with no differences over time. These findings support the use of either modality as viable management options for OL. Clinical Trial RegistrationBrazilian Clinical Trials Registry, identifier (RBR-7pgcyq).